Reproductive biology in the primitive relic Angiosperm Drimys brasiliensis (Winteraceae) - Gottsberger, Gerhard [UNESP]; Silberbauer-Gottsberger, Ilse [UNESP]; Ehrendorfer, Friedrich (Springer Nature, 1980)
From field observations on Drimys brasiliensis, principally in the Botucatu region of São Paulo State, Brazil, new data on the reproductive biology, the rhythm of growth, and the development of lateral cymose inflorescences, flowers and fruits are presented. Pollination accelerates the rate of flower-development for about 4-6 days. Pollination experiments show that D. brasiliensis is not self-sterile; because of mechanical devices the sticky pollen grains do not normally come into contact with the stigmata unless an animal pollen vector is involved. The pollinators are diurnal Coleoptera, Diptera and Thysanoptera which eat from the pollen, lick from the stigmatic exudates and (in case of the flies) probably also from the staminal glands. Fruit- and seedeaters are birds which seem to be the main dispersal agents. Establishment of new individuals normally is through seedlings, but also by vegetative propagation through plagiotropous branches which may root and separate from the mother plant. The morphological, developmental and reproductive aspects in D. brasiliensis are discussed in a wider context, compared with data from other Magnoliidae, and related to aspects of early Angiosperm evolution. © 1980 Springer-Verlag.
Keywords: Angiosperms; Development of inflorescences; Drimys brasiliensis; early Angiosperm evolution; flowers and fruits; pollination; reproductive biology; seed dispersal; vegetative propagation; Winteraceae